Effects of rural-to-urban migration on healthcare utilization of middle-aged and older adults: evidence from the China health and retirement longitudinal study - Xu, Lu; Chen, Yingchun (Frontiers in Public Health, 2025)
BackgroundAn increasing number of middle-aged and older adults are migrating from rural to urban areas for employment, to care for their younger generation and due to old age. As these age groups move into urban areas, their healthcare service utilization are directly related to their health status and basic rights to survival. It also places higher demands on China’s healthcare service provision.ObjectivesThis study aims to examine effects of rural-to-urban migration on healthcare utilization among middle-aged and older adults in China.MethodsPanel data from Waves 3, 4, and 5 of the China Health and Retirement Longitudinal Study were used. We included 318 participants in the exposure group and 7,525 participants in the control group. The study employed propensity score matching (PSM) and Difference in Difference (DID) analysis.ResultsDifference in difference regression results showed that middle-aged and older adults reduced number of hospitalizations when they moved to a city with DID values of −0.092 (p < 0.10) for the period 2015–2018 and − 0.135 (p < 0.05) for the period 2015–2020. No significant effects were observed regarding the number of outpatient visits (p > 0.05).ConclusionMiddle-aged and older migrants who migrated to cities reduced inpatient healthcare utilization, possibly due to lower hospitalization reimbursement rates, financial burden, and lower social integration. Policies enhancing health insurance reimbursement rates for migrants, integrated community support programs, and strengthening health education to promote health equity may provide remedy.